1980
DOI: 10.1111/j.1365-2494.1980.tb01510.x
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of root competition and shoot competition between Dactylis glomerata and Holcus lanatus

Abstract: Dactvlis glomerata and Holcus lanatus were grown together in boxes with either full competition, root competition only, shoot competition only or no competition between them. The boxes were either fertilized (150 kg ha^'N, 100 kg ha"'K, 80 kg ha" ' P) or not fertilized. The experiment was continued for 13 months, and a total of six cuts were taken.H. lanatus was more competitive than D. glomerata throughout the experiment, though the efTect declined after flowering during the second growing season. The effects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
1

Year Published

1984
1984
2002
2002

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(15 citation statements)
references
References 13 publications
1
13
1
Order By: Relevance
“…In both these studies no reversal of dominance of root competition after defoliation was observed. This may have been due to the fact that in the above studies the two species in competition were either both grasses (Remison and Snaydon, 1980) or both clovers (Scott and Lowther, 1980) and there may not have been large differences in the response of root growth to defoliation, shoot growth rates or canopy height and disposition, while in ihe present study there were large differences in the above attributes between the two species.…”
Section: Discussioncontrasting
confidence: 58%
See 1 more Smart Citation
“…In both these studies no reversal of dominance of root competition after defoliation was observed. This may have been due to the fact that in the above studies the two species in competition were either both grasses (Remison and Snaydon, 1980) or both clovers (Scott and Lowther, 1980) and there may not have been large differences in the response of root growth to defoliation, shoot growth rates or canopy height and disposition, while in ihe present study there were large differences in the above attributes between the two species.…”
Section: Discussioncontrasting
confidence: 58%
“…Numerous studies on Ihe nature of competition between species and populations of pasture plants (Donald, 1958;Rhodes, 1968;Snaydon, 1971;Eagles, 1972;Remison and Snaydon, 1980;Scott and Lowther, 1980), crops and weeds (Aspinail. 1960;Idris and Milthorpe, 1966), and cereaUcgume mixtures (Martin and Snaydon, 1982) have shown that the effects of root competition are usually greater than those of shoot competition, at least during the first few months after planting.…”
Section: Introductionmentioning
confidence: 99%
“…Because H. lanatus normally occurs on soils of moderate to low fertility (Remison and Snaydon 1980) we suspected that the plants of high nutrient treatments are possibly subjected to a stress situation due to a nutrient overdose. Therefore we formulated two specific hypotheses about the treatments a priori.…”
Section: Introductionmentioning
confidence: 99%
“…Optimal growth occurs in moist conditions; it grows well in very wet conditions and can survive moderate periods of drought (Watt 1978). H. lanatus occurs on soils of moderate to low fertility, but fertilisation appears to improve its competitive ability (Remison and Snaydon 1980). A. nigripes is an oligophagous miner that infests grasses from the tribes Glycerieae, Aveneae and Agrosteaea (Spencer 1990).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies on the nature of competition between crops and weeds (Remison and Snaydon 1980, Scott and Lowther 1980, Martin and Snaydon 1982, Martin and Field 1984, Kannangara and Field 1985, Bozsa and Oliver 1990, Satorre and Snaydon 1992, Qasem and Hill 1994 have shown that root competition has a greater effect on the relative performance of the species than does shoot competition. The present results are supportive of these studies.…”
Section: Maize±nutsedge Mixturementioning
confidence: 99%